STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN USAHA TANAMAN HORTIKULTURA DI UD. AKUR TANI DESA SIDOMULYO KECAMATAN SALAMAN KABUPATEN MAGELANG - Akbar wahyu, Wahyu Akbar Wicaksono (Yayasan Baitul Hikmah al-Zain, 2025)
This study analyzes community empowerment strategies through horticultural business development at UD. Akur Tani in Sidomulyo Village, Salaman District, Magelang Regency. By implementing targeted strategies, UD. Akur Tani assists the community in overcoming knowledge gaps, limited government support, and low awareness of horticultural innovation. This research employs a qualitative method with a field research approach, utilizing interviews, observations, and documentation. The findings indicate that the empowerment program positively impacts economic, social, and environmental aspects. Economically, it creates job opportunities; socially, it increases community awareness in land utilization; and environmentally, it promotes sustainable agricultural practices.